1971
DOI: 10.1063/1.1659709
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Growth of Cadmium on Polycrystalline Tungsten

Abstract: The multilayer adsorption and growth of cadmium on clean polycrystalline tungsten ribbons (with strong preferred orientation) has been investigated with a molecular-beam and mass-spectrometric technique. The adsorption and desorption kinetics have been studied as a function of temperature, supersaturation, and coverage. Five distinct adsorption states have been found between 100 and 600°C. Growth of bulk cadmium occurs only after multilayer adsorption is complete. No measurable supersaturation or critical nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1974
1974
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…PETN films on low surface energy substrates are characteristic of 3D island growth, whereas films on high surface energy substrates indicate two-dimensional layer growth . This is consistent with early observations of surface contamination effects on inorganic polycrystalline film growth . However, in inorganic film growth, the influence of the substrate and interfacial conditions becomes insignificant for layer growth beyond a few hundred nanometers.…”
Section: Results and Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…PETN films on low surface energy substrates are characteristic of 3D island growth, whereas films on high surface energy substrates indicate two-dimensional layer growth . This is consistent with early observations of surface contamination effects on inorganic polycrystalline film growth . However, in inorganic film growth, the influence of the substrate and interfacial conditions becomes insignificant for layer growth beyond a few hundred nanometers.…”
Section: Results and Discussionsupporting
confidence: 53%
“…94 This is consistent with early observations of surface contamination effects on inorganic polycrystalline film growth. 95 However, in inorganic film growth, the influence of the substrate and interfacial conditions becomes insignificant for layer growth beyond a few hundred nanometers. In this study, substrate effects on PETN film growth were shown to persist for thicknesses greater than 10 μm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The layer growth mode is sustained provided there is a continuous decrease in bonding energy between the layers from the first monolayer to the bulk-crystal value [17,36]. A classic example of layer growth is contamination-free homoepitaxial growth of semiconductor films [40], but it also occurs when depositing a low-meltingpoint metal on a high-melting-point metal [41].  Stranski-Krastanov growth develops when layer growth becomes unfavorable after the formation of one or more monolayers and island growth proceeds.…”
Section: Nucleation and Early Stages Of Growthmentioning
confidence: 99%